Poradnictwo edukacyjno-zawodowe jako działanie o charakterze optymalizującym tranzycję młodzieży z grup defaworyzowanych - Kozielska, Joanna (Pedagogika Społeczna Nova, 2023)
The article concerns the issue of educational and vocational guidance as an activity which optimize the transition of young people from disadvantaged groups from school to the labor market. In this group, due to environmental conditions, students of vocational schools were located and characterized. The basic assumption in the narration is to indicate that the choice of a profession is a momentous decision affecting many spheres of human functioning, so it is worth providing students from risk groups with intensified help from a career counselor.